2020
DOI: 10.1097/olq.0000000000001242
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Adolescent Girls and Young Women at High Risk for HIV Acquisition: A Risk Assessment Tool From the Girl Power-Malawi Study

Abstract: Background: Prioritizing HIV prevention for adolescent girls and young women (AGYW) at high risk of HIV acquisition in sub-Saharan Africa (typically considered ≥3 per 100 person years [PYs]) is urgently needed, but identifying these AGYW is challenging. We sought to assess and, if needed, enhance a risk assessment tool from the VOICE trial for identifying AGYW at high risk for HIV in Lilongwe, Malawi. Methods:A multisite prospective cohort study was conducted among sexually active AGYW 15-24 years old at four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…One additional conference abstract was available after initial screening, adding to a total of 13 risk score literature (9 peer-reviewed articles, 2 posters, 1 editorial letter, 1 abstract) that met the inclusion criteria and were included in this review (Figure 1) [5,6,[20][21][22][23][24][25][26][27][28][29][30]. Critical appraisal according to the PROBAST checklist concluded that one out of twelve models developed and two out of nine validated were of low risk of bias (Figure S1, Table S3 & S4).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One additional conference abstract was available after initial screening, adding to a total of 13 risk score literature (9 peer-reviewed articles, 2 posters, 1 editorial letter, 1 abstract) that met the inclusion criteria and were included in this review (Figure 1) [5,6,[20][21][22][23][24][25][26][27][28][29][30]. Critical appraisal according to the PROBAST checklist concluded that one out of twelve models developed and two out of nine validated were of low risk of bias (Figure S1, Table S3 & S4).…”
Section: Resultsmentioning
confidence: 99%
“…The majority (10 of 13) were RCTs or quasi-experimental studies that restricted recruitment and/or eligibility to specific at-risk population groups: (i) sexually active, contraceptionseeking women who attended the family-planning, STIs or research clinics (7 of 10, all RCTs) [5,6,[20][21][22][23][24], or (ii) school-attending AGYW (3 of 10) [25][26][27]. The remaining three were large-scale cohort studies or community trials that recruited all consenting members within the communities [28][29][30].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations